Intramedullary nailing of tibial shaft fractures in the semi-extended position using a suprapatellar approach: A retrospective case series. (November 2018) - Cazzato, G.; Saccomanno, M.F.; Noia, G.; Masci, G.; Peruzzi, M.; Marinangeli, M.; Maccauro, G.
Abstract: Tibial shaft fractures are extremely common injuries. High rate of union, acceptable alignment in all planes, and a low complication rate have been reported when diaphyseal fractures are treated by intramedullary nailing. However, knee pain after tibial nailing has historically been problematic. While the exact aetiology of the knee pain is still unknown, surgical approach relative to the patellar tendon, nerve transection, violation of the fat pad or joint capsule as well as nail diameter and implant prominence have been claimed as possible causes. Therefore, establishing an appropriate starting point remains a crucial step in the surgical procedure. Recently, suprapatellar nailing in the semi-extended position has been suggested as a safe and effective surgical technique. Literature is lacking on this topic, therefore the present article discusses clinical outcomes of 25 patients treated by suprapatellar nailing at 2 years follow up and a literature review.